Aerial 540° reverse hook kick in taekwondo: timing aspect - Volskiy, V. V.; Rogozhnikov, M. A.; Dementiev, K. N. (Theory and Practice of Physical Culture, 2017)
Our analysis of 120 video captures of freestyle taekwondo bouts (men and women) in the World and European championships for the period of 2014 to 2016 showed the aerial 540° reverse hook kick being widely applicable (in 93% of the bouts in fact). We found this kicking technique being one of the most popular in the freestyle programs.